OPTIMIZATION OF A PROTOCOL FOR THE EVALUATION OF LD50 INTenebrio molitor LARVARS USING COMMERCIAL ANTIFUNGALS AS A REFERENCE FOR THE TRIAL OF NEW COMPOUNDS (Editora Impacto Científico, 2025)
The growing demand for ethical, economical and sustainable methodologies has driven the development and validation of alternative models to the use of animals in scientific experimentation. In this context, the principle of the 3Rs (reduction, replacement and refinement) has become a fundamental guideline and has been adopted by the main regulatory legislations, such as the Arouca Law in Brazil and the OECD (Organization for Economic Cooperation and Development) guidelines. The historical milestones and regulatory evolution of alternative methods were discussed, as well as the available in vitro, in silico and in vivo models. The aim of this study was to optimize a protocol for determining the median lethal dose (LD50) using Tenebrio molitor larvae exposed to commercial antifungals, used in this work as a model substance. We highlight the use of T. molitor as a promising experimental model due to its practical handling, low cost, immunological robustness and physiological similarities to vertebrates. The toxicity of the drugs amphotericin B, caspofungin and itraconazole was also addressed, considering their mechanisms of action, therapeutic spectrum and adverse effects. The adaptation of the experimental protocol based on Brai et al. (2023) aims to establish an effective and reproducible tool for preliminary toxicological screening, enabling its future application in assessing the toxicity of new compounds with therapeutic potential. The results indicated a LD50 of 750 mg/kg for the three antifungals tested, with no statistically significant difference between them (p > 0.05). This approach contributes to the advancement of more ethical, reliable and accessible preclinical strategies, strengthening the use of alternative models in scientific research.